Attitudes of psychotherapists towards their own performance and the role of the social comparison group: The self-assessment bias in psychodynamic, humanistic, systemic, and behavioral therapists - Probst, Thomas; Humer, Elke; Jesser, Andrea; Pieh, Christoph (Frontiers in Psychology, 2022)
Previous studies have shown that psychotherapists overestimate their own professional performance (self-assessment bias). This study aimed to examine if the self-assessment bias in psychotherapists differs between therapeutic orientations and/or between social comparison groups. Methods: Psychotherapists gave subjective estimations of their own professional performance (0-100 scale from poorest to best performance) compared to two social comparison groups (“all psychotherapists” vs. “psychotherapists with the same therapeutic approach”). Moreover, they were asked about ratings (0–100% scales) on the number of their own patients recovering, improving, not changing, or deteriorating. In total, N=229 Austrian psychotherapists of four therapeutic orientations participated in the online survey (n=39 psychodynamic, n=121 humanistic, n=48 systemic, n=21 behavioral). Psychotherapists rated their own performance on average at M=79.11 relative to “all psychotherapists” vs. at M=77.76 relative to “psychotherapists with the same therapeutic approach” (p < .05). There were no significant differences between therapeutic orientations, but the interaction effect between social comparison group and therapeutic orientation attained statistical significance (p<.05). Bonferroni-corrected post-hoc tests revealed that psychodynamic and humanistic therapists had a drop of self-assessment bias in social comparison group “same approach” vs. “all psychotherapists” (p < .05). Psychotherapists overestimated the proportion of patients recovering (M = 44.76%), improving (M=43.73%) and underestimated the proportion of patients not changing (M=9.86%) and deteriorating (M=1.64%), whereby no differences between orientations emerged. A major drawback of this study is that results have not been connected to patient-reported outcome parameters or objectively rated performance parameters.